Kritik Feminis Poskolonial terhadap Representasi Masyarakat Adat dalam Film Dokumenter Pesta Babi - Dede Rohman; Kardina Kardina (Spektrum, 2026)
This article analyzes the documentary film Pesta Babi: Kolonialisme di Zaman Kita as a visual-political text that criticizes developmental colonialism in South Papua. Rather than treating the film solely as a medium of Indigenous advocacy, the article employs postcolonial feminist International Relations to examine how Indigenous communities are represented, whose voices are authorized to speak, and which gendered and generational experiences remain marginal within the narrative. The study uses a qualitative design and critical discourse analysis of verbal narration, visual sequences, actor construction, testimony, and the causal relations established between development, deforestation, dispossession, and everyday insecurity. The documentary constitutes the primary data, while recent journal literature, policy documents, and international standards on Indigenous rights provide contextual triangulation. The findings demonstrate that Pesta Babi effectively reverses state-centered narratives of food and energy development by foregrounding customary land, forest, local food systems, and Indigenous political agency. Nevertheless, the film still tends to construct Indigenous peoples as a relatively homogeneous collective subject and gives limited analytical space to differences of gender, generation, customary authority, and socioeconomic position. A postcolonial feminist reading therefore extends the critique of developmental colonialism to bodies, water, food provision, care work, family relations, and local ecological knowledge. The article argues that such criticism does not weaken the film's advocacy; it strengthens it by demanding more accountable, plural, and situated visual representation.